Les résidences secondaires sur la côte Pacifique Sud du Nicaragua : une stratégie de développent et ses conséquences - Xavier Matteucci; Matthias Beyer (Études Caribéennes)
In recent years, there has been a proliferation of second home developments on attractive coastal regions of Central and South America. Based on the assumed benefits of second home tourism to regional economies, public authorities - accompanied by private investors – have capitalised on this sector as part of their tourism development strategies. This paper first examines the nature of recent second home tourism developments and then presents the socio-economic and environmental impacts of this phenomenon as experienced by local communities on the South Pacific Coast of Nicaragua. The main impacts include conflicts with local and indigenous communities over land use and ownership, seasonal and low-income employment generation, an increased burden on municipal budget to provide public infrastructure, and environmental degradation. It is argued that the second home tourism sector, strongly driven by private real estate investors, fails to generate tourism activities which are expected to sustain community development. Furthermore, this study indicates that municipalities concentrating on the second home tourism segment may deprive themselves of access to resources for more sustainable forms of tourism activities.